Race and Reunion The Civil War in American Memory - BLIGHT, David W. (Harvard University Press, 2022)
No historical event has left as deep an imprint on America's collective memory as the Civil War. In the war's aftermath, Americans had to embrace and cast off a traumatic past. David Blight explores the perilous path of remembering and forgetting, and reveals its tragic costs to race relations and America's national reunion